Peran enzim dalam proses metabolisme seluler pada tumbuhan - Fanani, Silvi Nuriyah (Maliki Interdisciplinary Journal, 2025)
Enzymes play a very important role in cellular metabolic processes in plants. As biological catalysts, enzymes speed up chemical reactions that occur in cells without being permanently involved in these reactions. Without enzymes, chemical reactions in cells would proceed very slowly, which could inhibit various vital processes in plants. Therefore, the presence of enzymes is very necessary to maintain the smoothness and efficiency of cellular metabolism which supports plant growth and development. One prime example of the role of enzymes in plant metabolism is in photosynthesis, the process by which plants convert light energy into usable chemical energy. Enzymes such as ribulose bisphosphate carboxylase/oxygenase (RuBisCO) play a central role in the Calvin cycle, which converts carbon dioxide into organic compounds. In addition to photosynthesis, enzymes are also involved in cellular respiration, where energy stored in organic compounds, such as glucose, is converted into ATP through a series of enzymatic reactions such as glycolysis, the citric acid cycle, and the electron transport chain. In addition, enzymes function in the biosynthesis process of other important compounds, such as amino acids, carbohydrates and lipids. These compounds are necessary for cell growth, formation of cell structures, and maintenance of plant tissue. Without enzymes, these processes will not occur optimally, which can hinder the plant's ability to develop and survive. A deep understanding of the mechanism of action of enzymes in cellular metabolism is very important, especially in the field of agricultural biotechnology, to develop plants that are more efficient, more resistant to stress, and capable of producing more abundant products.